2017
DOI: 10.1016/j.jaci.2016.06.041
|View full text |Cite
|
Sign up to set email alerts
|

The IgE and basophil responses to Ara h 2 and Ara h 6 are good predictors of peanut allergy in children

Abstract: Thymic stromal lymphopoietin downregulates filaggrin expression by signal transducer and activator of transcription 3 (STAT3) and extracellular signal-regulated kinase (ERK) phosphorylation in keratinocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 12 publications
6
40
0
1
Order By: Relevance
“…13,14 In contrast, in a recent study in children from our associated children hospital, we found a higher AUC for Ara h 2 compared to Ara h 6. 1 In our previous study with adult subjects, partly overlapping with the one from this study, we found very similar results for Ara h 2 and 6. 10 In all studies, however, the differences in discriminative ability between Ara h 2 and 6 remain small.…”
Section: Discussionsupporting
confidence: 89%
“…13,14 In contrast, in a recent study in children from our associated children hospital, we found a higher AUC for Ara h 2 compared to Ara h 6. 1 In our previous study with adult subjects, partly overlapping with the one from this study, we found very similar results for Ara h 2 and 6. 10 In all studies, however, the differences in discriminative ability between Ara h 2 and 6 remain small.…”
Section: Discussionsupporting
confidence: 89%
“…Ara h 2 and Ara h 6 have proven to be 2 of the most informative peanut allergens in the diagnosis of peanut allergy, as most patients have specific IgE against 1 or both allergens . In addition, the current study shows that 80% of the 15 peanut‐allergic patients studied were sensitized to 1 or multiple isoforms of a third recombinant 2S albumin member Ara h 7, mostly in combination with recombinant Ara h 2.0201 or Ara h 6.01.…”
Section: Discussionmentioning
confidence: 58%
“…To date, 17 peanut allergens (Ara h 1‐17) are known and most of them have been sequenced and cloned . Previous research indicated that screening for specific IgE against 2S albumins Ara h 2 and 6 to date is most effective in diagnosing peanut allergy, as the majority of peanut‐allergic patients have specific IgE against these allergens . Ara h 2 and Ara h 6 are both proteins belonging to the conglutin family, and Ara h 6 has approximately 53% sequence identity with Ara h 2 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the BAT might be useful if clinical history, SPT and/or sIgE measurement are inconsistent or in addition an oral food challenge is not possible [42]. Furthermore, the use of recombinant allergens in the BAT might have added value in discriminating between clinically relevant and mere sensitization [44, 45] and should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%